Improving Critical Thinking Skills of Elementary Students Through Science Learning with Interactive Teaching Materials and Problem Based Learning - Nofitri, Fifi; Desyandri; Eriyanti, Fitri; Yerizon (Postgraduate, University of Mataram, 2024)
This study aims to evaluate the effectiveness of interactive multimedia-based learning with Problem Based Learning (PBL) model in improving critical thinking skills of elementary school students in Natural and Social Sciences subjects. This research uses a development method with quantitative and qualitative approaches. The results of validation from the aspects of material, media, and language showed high ratings, and the product was declared practical by teachers and students. Students were actively involved in learning, and the results of statistical analysis showed significant differences between the control group and the experimental group in learning activities. This shows that this method is effective in improving students' critical thinking skills. Nonetheless, this study has limitations in terms of generalization of the results. Future research is expected to expand the scope of the study and consider additional factors for the development of more effective learning methods.